Developing for Apple TV using tvOS and Swift - Bennett, Gary; Lees, Brad; Kaczmarek, Stefan (Apress : Imprint: Apress, 2015)
Gary Bennett, Brad Lees, and Stefan Kaczmarek, the team behind Swift 2 for Absolute Beginners, brings you a hands-on "Swift" introduction to the new tvOS SDK with a collection of app projects to try out. You'll learn how to create a BookStore app for the TV, including using Stack Views for book details, how to create a photo gallery app, and how to use collection view and split view controllers with a music collection app. Finally, you'll also learn how to store Apple TV app data in iCloud. The new Apple TV is here, and it's open for your native apps - Developing for the Apple TV with tvOS and Swift will get you started developing right away. What you will learn: How to use stack views in tvOS How to use collection views and split view controllers How to store Apple TV app data in iCloud How to create native apps for books, photos, and music on the Apple TV Who this book is for: Intermediate iOS developers who want to create native Apple TV apps using the new tvOS SDK.